Efektivitas Modul Ajar Berdiferensiasi Berbasis Sad Kerti Loka Bali pada Mata Pelajaran IPAS untuk Meningkatkan Kompetensi 4C Siswa - Putu, Agus Trisna (Wahana Pendidikan, 2026)
This study aims to examine the effectiveness of a differentiated instructional module based on Sad Kerthi Loka Bali in the Science and Social Studies (IPAS) subject for enhancing 4C Competencies (Critical Thinking, Creativity, Collaboration, Communication) among fifth-grade students in Cluster II, Busungbiu District during the 2024/2025 academic year. Employing a quantitative post-test-only control group design, data were collected through observations, interviews, and 4C competency questionnaires. The research population comprised all fifth-grade students (N=69) in Cluster II elementary schools, with a sample of 35 students divided between SD Negeri 1 Kedis (experimental group) and SD Negeri 3 Kekeran (control group). Data analysis commenced with normality and homogeneity tests, followed by t-test analysis (significance level α<0.05) of post-test results to determine the module's effectiveness in integrating Sad Kerthi Loka Bali values. The findings demonstrate that the differentiated instructional module significantly improved students' 4C competencies (Sig. [2-tailed] = 0.000 < 0.05). These results indicate that the locally-grounded Sad Kerthi Loka Bali-based IPAS module effectively enhances 4C competencies among fifth-grade students in Busungbiu District's Cluster II elementary schoolsThis study aims to e$xamine$ the$ e$ffe$ctive$ne$ss of a diffe$re$ntiate$d instructional module$ base$d on Sad Ke$rthi Loka Bali in the$ Scie$nce$ and Social Studie$s (IPAS) subje$ct for e$nhancing 4C Compe$te$ncie$s (Critical Thinking, Cre$ativity, Collaboration, Communication) among fifth-grade$ stude$nts in Cluste$r II, Busungbiu District during the$ 2024/2025 acade$mic ye$ar. E$mploying a quantitative$ post-te$st-only control group de$sign, data we$re$ colle$cte$d through obse$rvations, inte$rvie$ws, and 4C compe$te$ncy que$stionnaire$s. The$ re$se$arch population comprise$d all fifth-grade$ stude$nts (N=69) in Cluste$r II e$le$me$ntary schools, with a sample$ of 35 stude$nts divide$d be$twe$e$n SD Ne$ge$ri 1 Ke$dis (e$xpe$rime$ntal group) and SD Ne$ge$ri 3 Ke$ke$ran (control group). Data analysis comme$nce$d with normality and homoge$ne$ity te$sts, followe$d by t-te$st analysis (significance$ le$ve$l α<0.05) of post-te$st re$sults to de$te$rmine$ the$ module$'s e$ffe$ctive$ne